Hydrophobic catalyst for preparing methanol through carbon dioxide hydrogenation and preparation method thereof

By preparing hydrophobic Cu/ZnO/ZrO2 catalyst, the problems of low raw material conversion rate and poor water-heat resistance of the catalyst during CO2 hydrogenation and methanol production are solved, the high activity and long life of the catalyst are achieved, and the CO2 conversion rate and resistance are improved. Thermal retention rate.

CN119215905AActive Publication Date: 2024-12-31NINGBO JINYUANDONG PETROCHEM ENG TECH

Patent Information

Application Number
CN202411248776.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-31
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The conversion rate of raw materials during the hydrogenation of CO2 is low and the catalyst has poor water-heat resistance, resulting in catalyst deactivation and short service life.

Method used

By using the preparation method of a hydrophobic Cu/ZnO/ZrO2 catalyst, a catalyst with high water heat resistance is formed by mixing the precursors of copper, zinc and zirconium and ball milling and laser irradiation.

Benefits of technology

It improves the activity and selectivity of the catalyst, extends the service life of the catalyst, and shows good hydrothermal tolerance in the preparation of methanol by CO2 hydrogenation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215905A_ABST
    Figure CN119215905A_ABST
Patent Text Reader

Abstract

A preparation method of a hydrophobic catalyst for preparing methanol through hydrogenation of carbon dioxide comprises the following steps: (1) uniformly stirring and mixing a proper amount of precursors of copper, zinc and zirconium to obtain a precursor material; (2) putting the precursor obtained in the step (1) into a grinding tank, adding a proper amount of solvent, and simultaneously putting grinding balls into the grinding tank for grinding to obtain a ground material after the grinding is completed; (3) drying and roasting the ground material obtained in the step (2) to obtain a sample; and (4) carrying out laser irradiation treatment on the sample obtained in the step (3) to obtain the hydrophobic Cu / ZnO / ZrO2 catalyst. The catalyst prepared by the method has better activity and hydrothermal tolerance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for green methanol production, and in particular to a hydrophobic catalyst for producing methanol by hydrogenating carbon dioxide and a preparation method thereof. Background Art The combustion of fossil fuels (such as coal, oil and natural gas) is mainly used in various aspects closely related to human production and life, such as power generation, transportation and industrial production, but it also produces a large amount of carbon dioxide gas. As the main greenhouse gas, carbon dioxide poses a serious threat to the balance of the ecosystem, so it is urgent to find a green and efficient way to convert carbon dioxide. George A. Olah, the 1994 Nobel Prize winner in Chemistry, pointed out that the cycle model of synthesizing methanol by hydrogenation with carbon dioxide as raw material provides a new solution to the problem of fossil resource shortage.

[0003] The process of producing methanol by hydrogenation of CO2 not only reduces the greenhouse gas CO2, but also the high value-added product methanol can be widely used in human production. Therefore, the reaction system of producing methanol by catalytic hydrogenation of CO2 has great research significance and broad application prospects. In the process of producing methanol by hydrogenation of CO2, there is a problem of low raw material conversion rate. Studies have found that the selective regulation of products and catalyst performance are the key factors restricting the efficient preparation of methanol. Compared with the traditional synthesis gas (CO / H2) to produce methanol, the reaction heat release of CO2 hydrogenation to produce methanol is less, but water as a by-product can easily accelerate the sintering of copper nanocrystals and the pulverization of formed catalyst particles, resulting in the deactivation of the catalyst and a short service life. Therefore, this process requires higher hydrothermal resistance of the catalyst. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a hydrophobic catalyst for producing methanol by hydrogenation of carbon dioxide and a preparation method thereof. The catalyst obtained by the method has good hydrothermal resistance, prolongs the service life of the catalyst, and has good activity and selectivity.

[0005] The present invention solves the above technical problems through the following technical solutions: A method for preparing a hydrophobic catalyst for preparing methanol by hydrogenating carbon dioxide comprises the following steps: (1) Stirring and mixing appropriate amounts of copper, zinc and zirconium precursors to obtain a precursor material; (2) placing the precursor obtained in step (1) in a grinding jar, adding an appropriate amount of solvent, and simultaneously placing grinding balls in the grinding jar for grinding, and obtaining a ground material after the grinding is completed; (3) drying and roasting the ground material obtained in step (2) to prepare a sample; (4) The sample obtained in step (3) is subjected to laser irradiation treatment to obtain a hydrophobic Cu / ZnO / ZrO2 catalyst.

[0006] Furthermore, the molar ratio of the metal elements Cu:Zn:Zr in the copper, zinc and zirconium precursors is 6:2-4:1-5; the copper, zinc and zirconium precursors are copper acetate, zinc acetate and zirconium acetylacetonate, respectively.

[0007] Furthermore, the precursor material of step (1) also includes modified silicon oxide. The specific preparation method of modified silicon oxide is as follows: dissolving silicon oxide and phenyltriethoxysilane in a benzene solvent, stirring evenly, and reacting at 30 to 60° C. for 1 to 4 hours; then dripping triethylamine for treatment, and then filtering and drying to complete the modification treatment; Preferably, the phenyltriethoxysilane is 10-20% of the mass of silicon oxide, and the concentration of triethylamine is 1 mol / L; Preferably, the modified silicon oxide accounts for 2% of the total mass of the precursor material.

[0008] Furthermore, the solvent obtained in step (2) is one or both of ethanol and isopropanol, and polyethylene glycol is also added to the solvent.

[0009] Furthermore, in step (2), the volume ratio of the precursor material to the solvent is 1:0.5-3; Preferably, the volume ratio of the precursor material to the solvent is 1:1.5.

[0010] Furthermore, during ball milling, the diameters of the grinding balls were 20 mm, 10 mm, and 5 mm, respectively; The rotation speed during ball milling is 100-600 r / min, and the total ball milling time is 6-12 h.

[0011] Furthermore, during the grinding process, the volume ratio of the grinding balls to the precursor material and the solvent is 3-5:1.

[0012] Furthermore, the calcination conditions in step (3) are as follows: a tubular furnace is used under air atmosphere, the gas flow rate is 100-300 mL / min, the heating rate is 1-10° C. / min, and the calcination is performed at 300-600° C. for 4-8 hours.

[0013] Furthermore, the laser irradiation conditions in step (4) are: carried out at room temperature, with a wavelength of 248 nm and a laser pulse energy density of 500 mJ / cm 2 The laser repetition frequency is 10 Hz, the pulse width is 30 ns, the pulse number is 1000-2000, and the sample is annealed under vacuum conditions for 0.5-2 hours after laser irradiation.

[0014] A hydrophobic catalyst for producing methanol by hydrogenating carbon dioxide is obtained according to the preparation method described above.

[0015] Compared with the prior art, the present invention has the following advantages: 1. The hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide provided by the present invention can enhance the interaction between different metal salt components by reasonable adaptation of the content of metal components and addition of solvent components during ball milling, and at the same time helps to improve the dispersion of different components, thereby improving the activity and stability of the catalyst.

[0016] 2. The hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide provided by the present invention, through laser irradiation and modification of silicon oxide, the special photothermal effect causes changes in the surface geometry and chemical properties of the material and the dual effects of the modification treatment, so that the catalyst forms a super-hydrophobic surface, which can show good hydrothermal tolerance in the reaction process of preparing methanol by hydrogenation of CO2, thereby extending the service life of the catalyst.

[0017] 3. The hydrophobic catalyst for producing methanol by hydrogenation of carbon dioxide provided by the present invention has a simple ball milling process, is scalable, low-cost and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 TEM image of the catalyst prepared in Example 1 of the present invention; Figure 2 TEM image of the catalyst prepared in Example 3 of the present invention; Figure 3 Schematic diagram of the catalyst evaluation device for the production of methanol by hydrogenation of CO2.

[0019] In the figure, 1. hydrogen flow; 2. carbon dioxide gas flow; 3. nitrogen flow; 4. methanol reactor; 5. water cooler; 6. circulating cooling water inlet pipe; 7. circulating cooling water outlet pipe; 8. gas-liquid separator; 9. gas chromatograph; 10. crude methanol collection pipeline. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1 (1) dissolving silicon oxide and phenyltriethoxysilane in a benzene solvent, stirring evenly, and reacting at 50° C. for 3 h; then dropping 1 mol / L triethylamine until precipitation is complete, and then filtering and drying to complete the modification treatment and obtain modified silicon oxide; Cu(CH3COO)2·H2O, Zn(CH3COO)2, and zirconium acetylacetonate are stirred and mixed evenly according to the molar ratio of metal elements Cu, Zn, and Zr of 6:3:1, and modified silicon oxide is added while stirring to obtain a precursor material, in which the mass proportion of modified silicon oxide in the precursor material is 2%.

[0022] (2) The precursor material obtained in step (1) is placed in a 125 ml corundum grinding jar (planetary ball mill PM100, Retsch), and isopropanol is added. The ratio of the volume of isopropanol to the volume of the precursor material is 1.5:1. 20% (volume ratio) of polyethylene glycol is added to the isopropanol. At the same time, 5, 50, and 300 grinding balls with diameters of 20 mm, 10 mm, and 5 mm, respectively, are placed in the grinding jar. The ball-to-material ratio is 4:1, the ball milling speed is 500 r / min, and the ball milling time is 8 h.

[0023] After the ball milling is completed, the grinding balls are taken out to obtain the ground material in the grinding jar.

[0024] (3) The ground material obtained in step (2) was dried in an oven at 105° C. for 12 hours. Then, the ground material was calcined at 450° C. for 6 hours in a tube furnace under air atmosphere conditions with a gas flow rate of 300 mL / min and a heating rate of 5° C. / min to prepare a sample.

[0025] (4) The sample obtained in step (3) was subjected to laser irradiation treatment. The laser irradiation was carried out at room temperature using a German Lambda Physik LPX305iF excimer laser, wherein the wavelength was 248 nm and the laser pulse energy density was 500 mJ / cm 2 , laser repetition frequency is 10 Hz, pulse width is 30 ns, and pulse number is 1000. After laser irradiation, the sample is placed in a vacuum (10 - 5 mbar) and annealed at 300 degrees for 1 hour to obtain a hydrophobic catalyst.

[0026] Figure 1 This is a transmission electron microscope image of the catalyst of Example 1. Analysis of the electron microscope image shows that the catalyst nanocrystals prepared by ball milling and laser irradiation are small and generally distributed in the range of 5-10 nm.

[0027] Example 2 The technical point different from Example 1 is that the molar ratio of Cu:Zn:Zr is 6:3:3.

[0028] Example 3 The technical points different from Example 1 are that the number of pulses is 2000 and the sample is vacuum (10 -5 mbar), annealed at 300 degrees for 2 hours.

[0029] Figure 2 This is a transmission electron microscope image of the catalyst of Example 3. Analysis of the electron microscope image shows that the catalyst nanoparticles are generally smaller than 10 nm and are evenly distributed.

[0030] Comparative Example 1 The molar ratio of Cu:Zn:Zr is 6:1:0.5, and the other preparation processes are the same as those in Example 1.

[0031] Comparative Example 2 The laser treatment in step (4) is not used, and the other preparation methods are the same as those in Example 1.

[0032] Comparative Example 3 In step (2), polyethylene glycol is not added, and the other steps are the same as those in Example 1.

[0033] Comparative Example 4 The silicon oxide in the precursor material has not been modified, and the other preparation methods are the same as those in Example 1.

[0034] The detection method of catalyst activity and selectivity needs to be provided The performance of the catalysts of Examples 1-3 and Comparative Examples 1-4 in preparing methanol by hydrogenation of carbon dioxide was systematically evaluated in a self-built evaluation device. The schematic diagram of the evaluation device is shown in FIG. Figure 3 As shown, a hydrogen flow 1, a carbon dioxide gas flow 2 and a nitrogen flow enter a methanol reactor 4 for a catalytic reaction. The catalyst is loaded in the methanol reactor 4. The reaction-completed material is cooled by a water cooler 5 and then enters a gas-liquid separator 8 for gas-liquid separation. The gas flows out from the upper end of the gas-liquid separator 8 and is analyzed by a gas chromatograph 9 to detect the gas components and the corresponding contents. The liquid flows out from the bottom of the gas-liquid separator 8 and enters a crude methanol collection pipeline 10 to discharge the crude methanol.

[0035] 1. Catalytic evaluation reaction: The ratio of H2:CO2:N2 in the reaction mixture is 72:24:4, the catalyst particle size is 20-40 mesh, the volume is 1 mL, the pressure is 50 bar, the temperature is 250 ° C, and the space velocity is 5000 h -1 Before the reaction started, the catalyst was first reduced in a H2 atmosphere (5% H2 + 95% N2) at a reduction space velocity of 5000 h -1 , pressure 10 bar, temperature 300 degrees, 1 hour, heating rate 5 degrees / minute.

[0036] During the reaction, the liquid product was sampled once every 3 hours and weighed to calculate the yield. After three samplings, the heat resistance procedure was started, the temperature was raised to 380°C and maintained for 5 hours. After the heat resistance was completed, the temperature was lowered to 250°C and the evaluation was continued for 6 hours. The heat resistance retention rate was the ratio of the liquid phase yield of the catalyst before and after heat resistance.

[0037] 2. Analysis method: Quantitative detection by gas chromatography, automatic injection, H2 as carrier gas, N2 as pneumatic valve driving gas, TDX-01 as chromatographic column, Porapak Q as chromatographic column for liquid product analysis, TCD detector, injection port temperature of 120°C, column temperature of 90°C, and detector temperature of 150°C.

[0038] The main products of the reaction are methanol and carbon monoxide. The catalytic performance of the catalyst in the hydrogenation of carbon dioxide to methanol is shown in Table 1.

[0039] The results in Table 1 show that the catalyst prepared by ball milling and laser irradiation has excellent catalytic performance in the process of preparing methanol by hydrogenation of carbon dioxide, such as the conversion rate of CO2, which is mainly due to the smaller particle size of the catalyst prepared by ball milling; at the same time, the catalyst has a good heat retention rate, mainly due to the fact that laser irradiation improves the hydrophobicity of the catalyst, thereby improving the hydrothermal resistance and service life of the catalyst.

[0040] Comparison of the results of the embodiment with those of comparative example 1 shows that when the molar ratio of Cu, Zn and Zr is within the range of the claims, the catalyst has better catalytic performance, especially CO2 conversion rate.

[0041] Comparison of Comparative Example 2 with Example 1 shows that the introduction of the laser irradiation step greatly improves the heat resistance retention rate of the catalyst, mainly due to the improvement of the hydrophobicity of the catalyst.

[0042] In the catalyst prepared in Comparative Example 4, the modifying agent of silicon oxide was changed to hexamethyldisilazane, resulting in a decrease in the heat resistance retention rate of the catalyst.

[0043] Comparison between Comparative Example 3 and the embodiment shows that, during the ball milling process, a suitable solvent and material ratio can help improve the conversion rate of the catalyst in the process of carbon dioxide hydrogenation.

[0044] The performance index test results of the catalysts prepared in specific examples 1-3 and comparative examples 1-4 are shown in Table 1 below.

[0045] Table 1 Conversion rate (%) Methanol selectivity (%) Heat resistance retention rate (%) Example 1 25.3 82.2 88.9 Example 2 21.6 84.1 87.0 Example 3 24.1 81.9 92.1 Comparative Example 1 14.2 79.7 81.6 Comparative Example 2 22.8 78.0 61.4 Comparative Example 3 13.6 76.3 82.5 Comparative Example 4 23.7 77.9 74.2 From the test results in Table 1 above, changing the content of heavy metal elements in the catalyst precursor and changing the composition of the solvent during the ball milling process will affect the CO2 conversion rate of the catalyst; while the modification of silicon oxide and laser irradiation treatment have no obvious effect on the CO2 conversion rate of the prepared catalyst, but its heat retention rate is significantly better.

Claims

1. A method for preparing a hydrophobic catalyst for hydrogenating carbon dioxide to methanol, characterized in that: The steps include: (1) Stir and mix appropriate amounts of copper, zinc and zirconium precursors to obtain a precursor material; (2) placing the precursor obtained in step (1) in a grinding jar, adding an appropriate amount of solvent, and simultaneously placing grinding balls in the grinding jar for grinding, and obtaining a ground material after the grinding is completed; (3) drying and roasting the ground material obtained in step (2) to prepare a sample; (4) The sample obtained in step (3) is subjected to laser irradiation treatment to obtain a hydrophobic Cu / ZnO / ZrO2 catalyst.

2. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The molar ratio of the metal elements Cu:Zn:Zr in the copper, zinc and zirconium precursors is 6:2-4:1-5; the copper, zinc and zirconium precursors are copper acetate, zinc acetate and zirconium acetylacetonate respectively.

3. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The precursor material of step (1) also includes modified silicon oxide. The specific preparation method of modified silicon oxide is as follows: dissolving silicon oxide and phenyltriethoxysilane in a benzene solvent, stirring evenly, and reacting at a temperature of 30 to 60° C. for 1 to 4 hours; then dripping triethylamine for treatment, and then filtering and drying to complete the modification treatment; Preferably, the phenyltriethoxysilane is 10-20% of the mass of silicon oxide, and the concentration of triethylamine is 1 mol / L.

4. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The solvent obtained in step (2) is one or both of ethanol and isopropanol, and polyethylene glycol is also added to the solvent.

5. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The volume ratio of the precursor material to the solvent in step (2) is 1:0.5-3; Preferably, the volume ratio of the precursor material to the solvent is 1:1.

5.

6. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: During ball milling, the diameters of the grinding balls were 20 mm, 10 mm, and 5 mm; The rotation speed during ball milling is 100-600 r / min, and the total ball milling time is 6-12 h.

7. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 6, characterized in that: During the grinding process, the volume ratio of grinding balls to precursor materials and solvent is 3-5:

1.

8. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The calcination conditions in step (3) are as follows: a tubular furnace is used under air atmosphere, the gas flow rate is 100-300 mL / min, the heating rate is 1-10°C / min, and the calcination is performed at 300-600°C for 4-8 hours.

9. The method for preparing a hydrophobic catalyst for preparing methanol by hydrogenation of carbon dioxide according to claim 1, characterized in that: The laser irradiation conditions in step (4) are: carried out at room temperature, with a wavelength of 248 nm and a laser pulse energy density of 500 mJ / cm 2 , the laser repetition frequency is 10 Hz, the pulse width is 30 ns, the pulse number is 1000-2000, and the sample is annealed under vacuum conditions for 0.5-2 hours after laser irradiation.

10. A hydrophobic catalyst for hydrogenating carbon dioxide to methanol, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing super-hydrophobic silica

    CN101249964A

  • Hydrophobic copper-based catalyst, preparation method and application

    CN107519883A

  • Hydrophobic catalyst for synthesizing methanol through carbon dioxide hydrogenation and preparation method and application of hydrophobic catalyst

    CN112588320A

  • Catalyst for synthesizing methanol through hydrogenation of carbon dioxide, and preparation method and application thereof

    CN113368861A

  • Three-way catalyst prepared by mechanical ball milling method and used for preparing methanol through hydrogenation of carbon dioxide

    CN117443391A

Cited By

  • Hydrotalcite-like compound derived copper-zinc-aluminum-zirconium catalyst as well as preparation method and application thereof

    CN120205153A